(untitled) (Zoological Records and Reviews, 2022)
Predator-prey interactions are fundamental drivers of community structure and energy flow in freshwater ecosystems, regulating prey population sizes, shaping prey behavioural and morphological traits through predation pressure, and mediating trophic cascades that influence primary productivity. In tropical rivers and reservoirs, apex piscivores such as catfish, snakeheads, and murrels play critical roles in structuring fish community composition, yet the quantitative dynamics of their predator-prey interactions – including functional response curves, prey selectivity, diel predation patterns, and prey refugia use – are poorly documented in South Asian freshwater contexts. This study examines predator-prey interactions across three trophic levels in the Godavari river system, India, using stomach content analysis of 1,284 piscivore individuals, prey vulnerability index calculations, acoustic telemetry of predator-prey co-occurrence, and experimental mesocosm predation trials at 12 reservoir sites over two years (2021-2023). Apex piscivores show significant prey selectivity biased toward medium-sized prey fish (100-200 mm SL) and toward species with exposed habitat use. Prey fish show documented anti-predator behavioural responses including shoaling, habitat shifts, and reduced foraging rate in predator-exposed treatments. Invasive tilapia shows substantially lower predator avoidance behaviour than native prey species, potentially contributing to its dominance in predator-rich habitats. Conservation implications of apex predator decline for freshwater trophic cascade dynamics are discussed.